Partisipasi Masyarakat Dalam Pembangunan Desa Mulyasari Kecamatan Ciampel Kabupaten Karawang - Karmita Aji; Eka Yulyana; Evi Priyanti (Jurnal Pemerintahan dan Politik, 2022)
This research is motivated by the quality of an environment and the confort of the community in mulyasari village, ciampel district. The purpose of this study was to determine the participation of the mulyasari village community on factors such as supporting factors and inhibiting factors faced in infrastruvture development in mulyasari village, ciampel district. This research mothod uses descriptive qualitative research based on purpose sampling, data collection, interviews and documentation. The results of study showed that community participation in planning and decision-making in mulyasari village as a whole has been implemented, this can be seen in the participation carried out through the musrenbangdes.participation in implementation most of the people of mulyasari village are aware of the importance of the role of community participation in the form of community service workers, craftsmen and others in the from of food items, bamboos, stones and other forms of information on social media sources of funds for the implementation of infrastructure development sources ranging from village funds funds, provincial assistance village funds allocations, council aspirations, companies, and community. Participation in the utilization of the results, in this case regarding the percentage of success of village development policies in the infrastructure sector carried out in mulyasari village in general, can be said to be good, it can be seen from the roads that have been casted, the existence of drainage, mosques and sports fields and so on. Participation in the evaluation generally discusses what are the physical forms of infrastructure policies that have been made which are the results of policies that must be accounted for, both in the form of accountability reports and photo evidence of activities that see obstance of aactivities that see obstacles or problems that generally occur and seek solutions to exixting problem.Â Keyword: Community participation, Infrastructure, village Mulyasari